Effect of Ethanol Extract of Miana Leaves (Coleus atropurpureus L. Benth.) on the Growth of Pseudomonas aeruginosa and Staphylococcus epidermidis - Sufiah Asri Mulyawati; Angelia Harpahda; Mario Polo Widjaya (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
ABSTRACT Background: Nosocomial infections continue to present a significant challenge in healthcare systems due to their high prevalence and the increasing emergence of antibiotic resistance. The bioactive constituents of miana leaves (Coleus atropurpureus L. Benth.) exhibit potential antibacterial properties, supporting the need to evaluate the effectiveness of their ethanol extract in inhibiting the growth of pathogenic microorganisms. Purpose(s): to evaluate the ability of the ethanol extract of miana leaves (Coleus atropurpureus L. Benth.) to inhibit the growth of Pseudomonas aeruginosa. Methods: A post-test only control group design was employed using miana leaf extract (Coleus atropurpureus L. Benth.) as the treatment variable, cefadroxil as the positive control, and distilled water as the negative control against Pseudomonas aeruginosa, each tested in triplicate, and the antibacterial activity was evaluated using the disc diffusion method at concentrations of 1500 ppm, 2000 ppm, 2500 ppm, and 3000 ppm. Results: The ethanol extract of miana leaves (Coleus atropurpureus L. Benth.) demonstrated strong inhibitory activity against Pseudomonas aeruginosa at concentrations of 1500–3000 ppm, and the One-Way ANOVA results showed a significant difference (p < 0.05), indicating that the extract exhibits a measurable antibacterial effect against Pseudomonas aeruginosa in vitro. Conclusion: The ethanol extract of miana leaves (Coleus atropurpureus L. Benth.) effectively inhibits the growth of Pseudomonas aeruginosa, supported by strong antibacterial activity. Keywords: antibacterial; ethanol extract; Miana leaves (Coleus atropurpureus L. Benth); Pseudomonas aeruginosa